2013
DOI: 10.5483/bmbrep.2013.46.12.082
|View full text |Cite
|
Sign up to set email alerts
|

Identification of anti-adipogenic proteins in adult bovine serum suppressing 3T3-L1 preadipocyte differentiation

Abstract: Adipocyte differentiation is a complex developmental process forming adipocytes from various precursor cells. The murine 3T3-L1 preadipocyte cell line has been most frequently used in the studies of adipocyte differentiation. Differentiation of 3T3-L1 preadipocytes includes a medium containing fetal bovine serum (FBS) with hormonal induction. In this study, we observed that differentiation medium containing adult bovine serum (ABS) instead of FBS did not support differentiation of preadipocytes. Impaired adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…This observation suggests that other serum protein(s) or non-protein factor(s) regulate the function of tetranectin, which mediates the adipogenic effect of serum. In fact, ABS was shown to contain an anti-adipogenic protein(s) that suppresses adipocyte differentiation of 3T3-L1 cells, which might inhibit the adipogenic function of tetranectin [9]. In conclusion, proteins in FBS contain an adipogenic factor(s) that mediates the adipogenic effect of the serum.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This observation suggests that other serum protein(s) or non-protein factor(s) regulate the function of tetranectin, which mediates the adipogenic effect of serum. In fact, ABS was shown to contain an anti-adipogenic protein(s) that suppresses adipocyte differentiation of 3T3-L1 cells, which might inhibit the adipogenic function of tetranectin [9]. In conclusion, proteins in FBS contain an adipogenic factor(s) that mediates the adipogenic effect of the serum.…”
Section: Discussionmentioning
confidence: 93%
“…Fractionation of ABSppt from ABS also separated low-abundance proteins from most high-abundance proteins that remained in ABSsup. ABSppt constituted~30% of the total ABS protein content, which showed an adipogenic effect that suppressed adipocyte differentiation of 3T3-L1 cells as previously reported [9]. Therefore, putative adipogenic proteins in FBS were screened by comparative 2D-PAGE analysis of proteins in FBSppt and ABSppt.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This difference could be the result of the presence of stimulatory factors in NCS or inhibitory factors in FBS. Identification of such factors (as has been done for white adipocytes 10,11,46,47 ) and of the substances with which they interact on the target cells, can further our understanding of how circulatory factors influence brown adipose development and function. However, stimulatory factors putatively present in NCS may impede the identification of additional stimulatory factors, as differentiation may be already advanced.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have similarly reported increased adipogenic conversion of 3T3-L1 cells cultured in FBS as compared to adult bovine serum. 10,11 FBS is thus the most commonly used serum for most cell culture systems, and it is also the most common serum of choice for adipocyte cell line cultures. Probably therefore, it is often used even for primary brown adipocyte cultures (e.g.…”
Section: Introductionmentioning
confidence: 99%